The Importance of the Census of Anthropogenic Cavities in the Mitigation Geological Hazards: The Case of Grotte di Castro (Italy) - Gentili, Francesco; Madonna, Sergio; Nisio, Stefania (Geographies, 2025)
The municipality of Grotte di Castro (Lazio Region, Italy) has, for some time, been the subject of various studies concerning the census of artificial cavities. Recent combined applications of LiDAR and photogrammetric surveys have made it possible to develop specific methods for locating entrances and producing 3D models and georeferenced plans. The combined use of these models with geomechanical surveys supported by surface seismic surveys makes it possible to understand the state of health of these buried structures and whether, in the event of an earthquake or as a result of natural decay, they could pose a danger to the population. In this work, which builds on recent studies, a method for assessing the state of these cavities is proposed and tested, essentially to evaluate the risks of collapse and sinkholes. The final objective is to census and discover as many cavities as possible, not only for the mitigation of risk but also for the valorisation of these cavities, which represent a true historical and archaeological heritage—testimonies to the history and evolution of ancient Castrum Criptarum.